Answer:
i tried it by trial and error, and my work is below.
Step-by-step explanation:
2x + 9 = 23
subtract 9 from both sides
2x = 14
guess.... lol
x=7
Answer: PQ=15
Step-by-step explanation:
XY=(PQ+SR)/2
PQ+SR=2*XY
PQ+35=2*25
PQ+35=50
PQ=15
Subtract 2b by both sides which gets -b+4=-5 then subtract 4 by both sides so you get -b=-9 and divide -1 by both sides so that b=9
The moment-generating function for y is given as eⁿᵇ - eⁿᵃ / n(b-a) and derivation of moment-generating function of y is e-1/t
Given that,
The interval (0, 1) is covered by a uniform distribution of y, and a > 0 is a constant.
The moment generating function is eⁿᵇ - eⁿᵃ / n(b-a)
The given interval is (0,1)
Here a =0;
b=1;
Now substitute the values of a and b in the above moment generating function we get,
y=eⁿᵇ - eⁿᵃ / n(b-a)
y=e^1-e^0/t(1-0)
y= e-1/t
Therefore, the derivation of the moment generating function is e-1/t
Learn more about moment-generating function here:
brainly.com/question/15061360
#SPJ4